Buxus sempervirens and Laurus nobilis leaves from an archaeological site at 7300 cal BP (La Draga, Spain) provide a better understanding of past vegetation and human activities. (April 2021) - Castells, Eva; Araya-Piqué, Valentina; Behncké, Ada; Piqué, Raquel
Leaves are valuable, but very rare, remains in archaeological contexts, as they can provide precise information on the landscape vegetation composition, the past climatic conditions and the use of plant resources in a settlement. La Draga (Spain) is an early Neolithic site partially waterlogged, which has allowed the preservation of organic material. During the excavation of the oldest level (7300–7000 cal BP), we recovered 29 leaf samples in an optimal state of preservation. Here we explore the potential of these leaves as indicators both of the use of vegetation at the settlement and of past climatic conditions. Firstly, we determined the species identity by comparing the leaf morphological and microanatomical traits with those of contemporary individuals. Secondly, we analyzed the leaf stomatal patterning (stomatal density, index, and size) as proxies of paleoclimate during the Neolithic, when lower atmospheric CO2 and wetter conditions are documented. The leaves of La Draga were identified as Laurus nobilis and Buxus sempervirens, two evergreen species well documented at the site from other archaeobotanical records, such as charcoal and wooden implements. We found no differences in stomatal traits between the archaeological and the contemporary leaves of L. nobilis and B. sempervirens, which shows the limitation of stomatal frequency as proxies for CO2 . The presence of these species at the site provides good complementary data for past woodland vegetation composition and the production of wood implements. The wide distribution of L. nobilis leaves across the site suggests that this taxon was present in the riparian forest at the site surroundings. In contrast, leaves of B. sempervirens were grouped together, which might indicate that they belonged to the same branch, probably transported as raw material from nearby forests to the settlement. This study illustrates the value of archaeological leaves to provide a better understanding on the past vegetation and human activities.